(untitled) (Research, Society and Development, 2020)
Objective: To evaluate the knowledge of dentistry students at the Federal University of Campina Grande about concepts about the main bacterial infections with oral and / or maxillofacial manifestations. Method: It was an observational, descriptive study, with quantitative and qualitative analysis whose sample was composed of 130 students from the 1st, 2nd, 9th and 10th periods. A questionnaire of 12 objective questions was used about: syphilis, tuberculosis, leprosy and actinomycosis. The results were subjected to Pearson’s Chi-Square test. Results: Most participants were female (58%), aged between 18 and 33 years. Regarding the questions that characterized the etiologic agents of bacterial infections, a higher percentage of correct responses was observed in the 9th and 10th period group (p=0.002). When relating the characteristics of syphilis with their respective stages, it was observed that the percentage of error was only 6.15% of the total number of students, with no statistically significant difference (p=0.791) between the groups. In the analysis of possible oral manifestations of tuberculosis, it was observed that the percentage of error was 69.23% of the total number of students, with no statistically significant differences between groups (p=0.060). Most students stated that they acquired knowledge about these infections at the university (54.61%). A total of 63.07% self-assessed their knowledge on the subject as insufficient. Conclusion: Despite the contrary self-assessment, students showed satisfactory knowledge, mainly about the etiological agents of these diseases and about the stages of syphilis.